Computing native network (CNN) technology and application driven by joint communication ＆ computing (JC＆C) - Jie SUN; Leiming MA; Aidong YANG; Xiaozhou YE; Peng LYU; Zhigang WANG; Ye OUYANG (Dianxin kexue)
The global telecom industry is carrying out research and exploration of potential 6G technical architectures and key techs, of which it has become a consensus in the industry to further realize the vision of 6G smart inclusion by better enabling all new 6G network technologies and services through joint communication ＆amp; computing (JC＆amp;C).Therefore, how to realize the deep integration and real-time collaboration of communication and computing to meet the needs of ultra-low latency and real-time response of new services in dynamic and complex network environments has become the challenge and key of JC＆amp;C.A computing native network (CNN) driven by JC＆amp;C was proposed, which realized the decoupling of communication and computing of base station or multiple base stations, computing pooling and intelligent JC＆amp;C scheduling through computing time division multiplexing and intelligent JC＆amp;C scheduling, thus realizing the base station to support communication and computation services simultaneously.The technology has been technically verified and piloted, and the experimental and pilot results demonstrate that CNN can effectively improve the computing utilization rate of wireless networks and realize the base station to support communication and computing services simultaneously, facilitating the evolution of 6G JC＆amp;C.